2007
DOI: 10.1007/s00595-007-3484-x
|View full text |Cite
|
Sign up to set email alerts
|

Water-Clear Cell Parathyroid Adenoma Causing Primary Hyperparathyroidism in a Patient with Neurofibromatosis Type 1: Report of a Case

Abstract: Water-clear cell parathyroid adenoma is an exceedingly rare tumor, composed exclusively of tumor cells with abundant foamy cytoplasm. A combination of hyperparathyroidism and neurofibromatosis type 1 (NF1) is also a rare phenomenon. We report an 18-year-old woman with primary hyperparathyroidism caused by water-clear cell parathyroid adenoma in association with NF1. She had renal stones, hypercalcemia, and an elevated plasma level of intact parathyroid hormone. Physical examination revealed a palpable tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Most of the reports describes parathyroid adenoma as the cause of hyperparathyroidism (16)(17)(18)(19). We found one case report of the association between NF1 and parathyroid carcinoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reports describes parathyroid adenoma as the cause of hyperparathyroidism (16)(17)(18)(19). We found one case report of the association between NF1 and parathyroid carcinoma (20).…”
Section: Discussionmentioning
confidence: 99%
“…In 1 patient, there was concomitant multiple endocrine neoplasia type 1 (MEN-1); in 1 patient, neurofibromatosis type 1 (NF-1); and in all others, it was found to be sporadic. The most common adenoma localization was the left inferior parathyroid gland (n=10), followed by the right lobe upper pole (n=4) (4,12). In 1 patient, the lesion was reported to be located in the left thyroid lobe (8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rare form (1%) of water-clear cell hyperplasia (WCCH) of hyperparathyroidism was first described by Albright et al (3) in 1934. As adenoma in the etiology is even more uncommon, only 19 cases have been reported since 1994, and of those cases, adenoma was in both parathyroid glands in only one case (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 13 patients with NF1 and HPP have been described, but the pathogenesis of this association has not yet been well elucidated [12]. Dayle et al [6] reported the first cases in the literature, and presented the hypothesis that there could be a genetic link between parathyroid adenoma (originating in endoderm) and NF1 (originating in neuroectoderm).…”
Section: Discussionmentioning
confidence: 99%